Relationship between sanitation conditions and the sustainable development goals (Research, Society and Development, 2022)
Access to sanitation was adopted in 2015 by the United Nations Summit on Sustainable Development as one of the goals to be achieved globally by 2030. However, in a quick observation of the other Goals, it is noted that their scope also involves better sanitation conditions. This study aimed to identify the data obtained at the Trata Brasil Institute to correlate the behavior of income, health, infant mortality and education when the available conditions of access to basic services are modified, with a view to bringing its results closer to the Objectives proposed in the 2030 Agenda. Therefore, the coefficients of linear correlation and determination were determined and for the accomplishment of these calculations and the construction of the graphs the software RStudio was used. The correlations and the coefficients of determination calculated proved to be strong and capable of well explaining their variation as the existing forms of access to sanitation change. In other words, the indicators tend to improve when investments are made in the sector and the more the population is provided with access to water and sewage collection.